Poggetti Vecchi (Tuscany, Italy): A late Middle Pleistocene case of human–elephant interaction. Issue 133 (August 2019) - Aranguren, Biancamaria; Grimaldi, Stefano; Benvenuti, Marco; Capalbo, Chiara; Cavanna, Floriano; Cavulli, Fabio; Ciani, Francesco; Comencini, Giacomo; Giuliani, Claudia; Grandinetti, Giuditta; Mariotti Lippi, Marta; Masini, Federico; et al.
Abstract: A paleosurface with a concentration of wooden-, bone-, and stone-tools interspersed among an accumulation of fossil bones, largely belonging to the straight-tusked elephant Palaeoloxodon antiquus, was found at the bottom of a pool, fed by hot springs, that was excavated at Poggetti Vecchi, near Grosseto (Tuscany, Italy). The site is radiometrically dated to the late Middle Pleistocene, around 171, 000 years BP. Notable is the association of the artifacts with the elephant bones, and in particular the presence of digging sticks made from boxwood ( Buxus sp.). Although stone tools show evidence of use mainly on animal tissues, indicating some form of interaction between hominins and animals, the precise use of the sticks is unclear. Here we discuss about the role played by the hominins at the site: paleobiological and taphonomic evidence indicates that the elephants died by a natural cause and were butchered soon after their death. The associated paleontological and archeological evidence from this site provides fresh insights into the behavior of early Neanderthals in Central Italy. The discovery of Poggetti Vecchi shows how opportunistically flexible Neanderthals were in response to environmental contingencies.